Sliding bubble dynamics and the effects on surface heat transfer - ROBINSON, ANTHONY; MURRAY, DARINA (My University, 2012)
An investigation into the eff ects of a single sliding air bubble on heat transfer from a submerged, inclined surface has been undertaken. Existing literature has shown that both vapour and gas bubbles can increase heat transfer rates from adjacent heated surfaces. However, the mechanisms involved are complex and dynamic and in some cases poorly understood. The present study utilises high speed, high resolution, infrared thermography and video photography to measure two dimensional surface heat transfer and three dimensional bubble position and shape. This provides a unique insight into the complex interactions at the heated surface. Bubbles of volume 0.05, 0.1, 0.2 and 0.4 ml were released onto a surface inclined at 30 degrees to horizontal. Results con rmed that sliding bubbles can enhance heat transfer rates up to a factor of 9 and further insight was gained about the mechanisms behind this phenomenon. The enhancement e ects were observed over large areas and persisted for a long duration with the bubble exhibiting complex shape and path oscillations. It is believed that the periodic wake structure present behind the sliding bubble a ects the bubble motion and is responsible for the heat transfer e ects observed. The nature of this wake is proposed to be that of a chain of horseshoe vortices.
Journal of Physics: Conference Series
EUROTHERM 2012
PUBLISHED
Potiers, France
Keywords: single sliding air bubble; single sliding air bubble